Narrow Gap MAG Welding and Joint Performance Analysis of 25Cr2NiMo1V Thick Plate. Issue 1 (1st January 2022) - Qian, Xiaoyan; Ye, Xin; Hou, Xiaoqi; Wang, Fuxin; Li, Shaowei; Yu, Zhishui; Huang, Chen; Cui, Jinpeng; Zhu, Chunxiang
Abstract: The narrow gap MAG welding system was used to successfully weld the 50mm thick butt joint of 25Cr2NiMo1V rotor steel. After 15-layer bead welding, heat treatment is performed on the welded joint. Compare the changes in the microstructure, tensile strength and impact energy of the welded joints and the heat-treated joints at 580°C (20h). The results show that after the heat treatment of the structure, the side lath ferrite in the coarse-grained region grows up, and the eutectoid ferrite grows up in the fine-grained region first. The strength of the welded joint is about 605MPa, and the fracture is characterized by ductile fracture. After heat treatment at 580°C (20h), the strength is about 543MPa, the fracture is characterized by ductile fracture, and there are also a large number of discontinuous small surface platforms, and the characteristic of brittle fracture appears slightly. The impact energy of the weld center of the welded joint is about 141J, the fusion line area is about 113J, and the toughness of the fusion line is slightly lower than that of the weld center. After heat treatment, the impact energy at the center of the weld is about 183J, the fusion line area is about 95J, the toughness of the weld center increases, and the toughness of the fusion line decreases.